ANALYSIS OF THE CONCEPT OF BEAUTY IN PHRASEOLOGISMS IN UZBEK AND ENGLISH LANGUAGES - Rahimova Gulzoda Murotjon qizi; Hoshimova Nargis Abdullayevna (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
In this article, taking into account the communicative and methodological status of phraseological units, under the influence of the original units, their use in abnormal conditions for the translation language, the formation of combinations that are not allowed by the majority of the culture of the translation language, and sometimes We will consider the use of the concept of beauty in English and Uzbek, taking into account the fact that it can cause completely different interpretations of meaning and function.